Underground Pumped-Storage Hydropower (UPSH) at the Martelange Mine (Belgium): Interactions with Groundwater Flow - Estanislao Pujades (Energies, 2020)
Underground pumped-storage hydropower (UPSH) is a promising technology to manage the electricity production in flat regions. UPSH plants consist of an underground and surface reservoirs. The energy is stored by pumping water from the underground to the surface reservoir and is produced by discharging water from the surface to the underground reservoir. The underground reservoir can be drilled, but a more efficient alternative, considered here, consists in using an abandoned mine. Given that mines are rarely waterproofed, there are concerns about the consequences (on the efficiency and the environment) of water exchanges between the underground reservoir and the surrounding medium. This work investigates numerically such water exchanges and their consequences. Numerical models are based on a real abandoned mine located in Belgium (Martelange slate mine) that is considered as a potential site to construct an UPSH plant. The model integrates the geometrical complexity of the mine, adopts an operation scenario based on actual electricity prices, simulates the behavior of the system during one year and considers two realistic scenarios of initial conditions with the underground reservoir being either completely full or totally drained. The results show that (1) water exchanges may have important consequences in terms of efficiency and environmental impacts, (2) the influence of the initial conditions is only relevant during early times, and (3), an important factor controlling the water exchanges and their consequences may be the relative location of the natural piezometric head with respect the underground reservoir.